1972
DOI: 10.1099/00207713-22-4-241
|View full text |Cite
|
Sign up to set email alerts
|

Genome Size and Base Composition of Deoxyribonucleic Acid from Eight Human T-Mycoplasmas

Abstract: The base compositions of the deoxyribonucleic acid and the genome sizes of eight serotypes of human T-mycoplasmas are reported. The guanine plus cytosine contents, as measured by thermal denaturation and CsCl gradient centrifugation, are 27 t o 28%, the latter method iving slightly lower values. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
4
1

Year Published

1974
1974
2002
2002

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 7 publications
4
4
1
Order By: Relevance
“…The calculated genome size of the DNA from these same two T mycoplasmas was 4.7 X 10' and 4.4 X 10' daltons, respectively (2). All eight serotypes of human T mycoplasmas were similarly examined, and the calculated D N A genome size was found to range from 4.1 X lo8 t o 4.8 X lo8 daltons (8). These values were similar to those found in the sterol-requiring classical mycoplasmas.…”
supporting
confidence: 61%
“…The calculated genome size of the DNA from these same two T mycoplasmas was 4.7 X 10' and 4.4 X 10' daltons, respectively (2). All eight serotypes of human T mycoplasmas were similarly examined, and the calculated D N A genome size was found to range from 4.1 X lo8 t o 4.8 X lo8 daltons (8). These values were similar to those found in the sterol-requiring classical mycoplasmas.…”
supporting
confidence: 61%
“…Howard et al (13) reported a DNA G+C content of 27.9 mol% for feline strain 382, and we reported a DNA G+C content of 27.1 mol% for feline serogroup SI strain FT2-BT (= ATCC 49229T) (7); these values are consistent with the range of values (26.9 to 31.6 mol%) reported for all other Ureaplasma species or strains that have been examined (1,13). Thus, the combined morphological, biological, and biochemical data indicate that the seven feline strains belong to the genus Ureaplasma, and the combined antigenic, genomic (DNA homology and DNA cleavage patterns), and SDS-PAGE profiles indicate that the two feline groups are distinct and are unrelated to each other or to the three previously established Ureaplasma species and that each merits species status.…”
Section: Discussionsupporting
confidence: 79%
“…The values for the human strains T960 and 58 were 27.4 and 27.5 mol%, respectively. This compares with the values of 27.1 and 28.0 mol% reported by Black et al (3) and is within the range of 26.9 t o 28.0 mol% G+C content they found for for human T-mycoplasmas. These two human strains were included as controls to ensure that our results could be compared with those previously reported for the human strains (3).…”
supporting
confidence: 72%